PENGEMBANGAN MODUL BERNUANSA HASIL RISET PADA MATA KULIAH FISIOLOGI REPRODUKSI UNTUK MAHASISWA BIOLOGI - Arianti, Febri; Sumarmin, Ramadhan; Syukur, Ulfa (Kolaboratif, 2014)
One of materials that creates self-proficiency in learning is module. There are many important things in module that can be used for developing materials appropiate with college students’ needs, one of them is research about reproduction physiology. This research is development research by implementing Plomp models. The research was conducted to know the practicallity of nuanced research result module for college students of Biology Department. The validation of the module is categorized valid for didactic, construction, and technical aspect. The practicality of nuanced research result for lecturers is categorized very practical and the practicality for college students is practical in three aspects: ease usage, useful, and time aspect.